The pollination biology of two species of Helicteres (Malvaceae) with different mechanisms of pollen deposition - Franceschinelli, Edivani Villaron (Flora. Morphologie, Geobotanik, Oekophysiologie, 2005)
Species of Helicteres are pollinated mainly by hummingbirds and bats. Most species pollinated by hummingbirds have a mechanism of depositing pollen on the top of the pollinator's head such as is shown in this work for Helicteres sacarolha. H. brevispira has an unusual mechanism of depositing pollen grains under the tail or on the abdomen of the hummingbirds. The top of the birds’ head may be considered an efficient place to transport pollen grains, because it is plain, easily accessible for deposition and donation of pollen and not easily accessible for grooming, while the tail is movable and inclined. Thus, H. brevispira pollinators may carry or transfer fewer amounts of pollen grains than H. sacarolha pollinators from one flower to another. If a large amount of pollen grains is lost, a higher quantity of flower or pollen has to be produced to guarantee reproductive success. Plants of H. brevispira set higher number of flowers and pollen grains per flower than H. sacarolha and have also higher rates of fruit and flower abortion. Thus, pollination efficiency of H. brevispira may be reached by high pollen and flower production. Flower change mechanism presented in this species may be also involved with the optimization of pollinator feeding and pollination efficiency.